PERBANDINGAN MODEL COOPERATIVE, INTEGRATED, READING AND COMPOSITION (CIRC) DENGAN MODEL AUDITORY, INTELECTUALLY AND REPETITION (AIR) DITINJAU DARI AKTIVITAS DAN HASIL BELAJAR MEMBACA SISWA KELAS V SD GUGUS I KEC. BONTONOMPO KAB. GOWA - Sri Wahyuni Nengsi; Tarman; Andi Paida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is quantitative research with a quasi-experimental design type of research with the Nonequivalent Multiple-Group Design type which aims to find out whether there are differences in student activities and learning outcomes through the CIRC learning model and the AIR learning model. The population in this study were all students of class V, Cluster 1, Bontonompo District, which consists of four schools with a total of 72. The research sample chosen was 25 class V students of SDN Rappokaleleng and SDN Kalaserena, totaling 25 people using a purposive sampling technique. The data collection technique in the research was carried out through observation and test techniques. Observation was used to observe students through 6 indicators for assessing student activities with the results in the CIRC model being worth 71.22 and the AIR model being worth 74.22. The research results based on descriptive analysis showed that the average value of the CIRC learning model was 80.00. Meanwhile, when applying the AIR learning model, an average score of 86.80 was obtained, meaning that the AIR model improved more than the CIRC learning model, while the results of the inferential analysis showed that the AIR learning model had a more significant effect compared to the CIRC learning model on the reading learning outcomes of fifth grade elementary school students. Rappokaleleng and Kalaserena Elementary School. This is based on the results of the independent sample t test obtained, namely the sig value. 0.025 < 0.05.